(untitled) (Plant Bulletin, 2024)
Sugarcane is an important crop for sugar and bioenergy production and belongs to the family poaceae. Current sugarcane varieties have a highly complex and large genome, with 100-130 chromosomes. The demand for sugar, fiber, bagasse and molasses is increasing in Pakistan due to the rising population. Varieties of sugarcane (Saccharum officinarums L.) that are produced by breeding method take approximately 8-10 years, with the number of pests and diseases causing a decrease in cane yield. Improving the productivity of sugarcane varieties is a major challenge. Tissue culture is a way for quick multiplication of desired varieties and to develop disease free healthy plants. Therefore, using high-yielding sugarcane varieties can help us in increasing production. This research aimed to optimize embryogenic callus for subsequent regeneration in sugarcane varieties, specifically CPF-251, HSF-240, and CP-77-400 to device micropropagation. Callus induction was initiated in four week culture of explant developed from spindle leaves by employing various concentrations of plant growth regulators (PGRs) such as Kinetin (0.2 mgL-1, 0.3 mgL-1, 0.4 mgL-1) and 2, 4-D (1.5 mgL-1, 2.5 mgL-1, 3.5 mgL-1) on Murashige and Skoog (MS) medium. Micro shoots emerged after three weeks of callus culture of media supplemented with differing concentrations of BAP (0.3 mgL-1, 0.4 mgL-1, and 0.5 mgL-1) on MS medium. After three weeks, roots developed, when the shooting plants were placed in the rooting medium containing varying concentrations of PGRs such as IBA (0.3 mgL-1 0.4 mgL-1, 0.5 mgL-1) and NAA (3.5 mgL-1, 4.5 mgL-1, 5.5 mgL-1) on MS medium. The most effective shoot growth of variety HSF-240 was obtained at MS + BAP 0.5 mgL-1 + IBA 0.5 mgL-1 + NAA 5.5 mgL-1 with 4.9 cm shoot length, 2.1 cm length of root and 8 numbers of roots. Similarly, for variety CP-77-400, optimal shoot growth was observed at MS + BAP 0.4 mgL-1 + IBA 0.4 mgL-1 + NAA 4.5 mgL-1, with a shoot length of 3.9 cm, root length of 2 cm, and 6 numbers of roots. For variety CPF-251, the most conducive conditions for shoot growth were at MS + BAP 0.3 mgL-1 + IBA 0.3 mgL-1 + NAA 3.5 mgL-1, resulting in a shoot length of 3.5 cm, root length of 1.7 cm, and 5 numbers of root formation. Plants developed through this study proved useful for producing high-yielding, high-sugar recovery cane of existing commercial varieties.